The Routledge handbook of research methods in the study of religion - Engler, Steven, 1962-; Stausberg, Michael, 1966- (Routledge handbooks in religion, 2022)
This substantially revised second edition of The Routledge Handbook of Research Methods in the Study of Religion remains the only comprehensive survey in English of methods and methodology in the discipline. Designed for non-specialists and upper undergraduate-/graduate-level students, it discusses the range of methods currently available, to stimulate interest in unfamiliar methods and to enable students and scholars to evaluate methodological issues in research. The Handbook comprises 39 chapters - 21 of which are new, and the rest revised for this edition. 56 contributors from ten countries cover a broad range of topics divided into three clear parts: Methodology Methods Techniques. The first section addresses general methodological issues: including comparison, research design, research ethics, intersectionality, and theorizing/analysis. The second addresses specific methods: including advanced computational methods, autoethnography, computational text analysis, digital ethnography, discourse analysis, experiments, field research, grounded theory, interviewing, reading images, surveys, and videography. The final section addresses specific techniques: including coding, focus groups, photo elicitation, and survey experiments. Each chapter covers practical issues and challenges, theoretical bases, and their use in the study of religion/s, illustrated by case studies. The Routledge Handbook of Research Methods in the Study of Religion is essential reading for students and researchers in the study of religion/s, as well as for those in related disciplines.